Direct anterior composite restoration – a predictable outcome: сase report - Z. Döbrentey (Эндодонтия Today)
In accidents, anterior teeth frequently get injured. In such cases composite restoration can be used as a minimally invasive approach. For a predictable result, it is recommended to use a wax-up and a silicon index as guides to create the correct shape of the incisal. The right matrix system helps reproduce the approximal surface. For an aesthetic outcome, an anatomic layering technique should be used to create the correct optical effects of a natural tooth. Finally, finishing and polishing is responsible for the surface texture and life-like reflection.